Literatura Review: Educational Materials, Design, Health And Nursing (Research, Society and Development, 2023)
Objective: To verify the status of research in the area of interest of educational materials, design, health and nursing. Methodology: This is a literature review developed with articles published from 2010 to 2020 in electronic databases: SciELO, Google Scholar, Scopus, VHL Regional Portal (Virtual Health Library) and UFC Repository (Federal University of Ceará). Results: The object of study treated by all the articles observed were educational booklets, varying only between the supports, printed, digital, games, software, educational technologies, folders, the vast majority in printed formats. The themes addressed issues such as diabetes, hypertension, obesity, breastfeeding, the elderly, pediatrics, pregnancy, food, HIV, HTLV, STDs, burns, leprosy, first aid and health education issues. Only 6 presented only the construction of the booklet, 14 presented only the validation and all the others presented the two processes, construction and validation of the educational material addressed. Those who presented percentage data ranged from 70 to 100% in material validation and indices from 0.7 to 0.99. Conclusion: The results presented by all articles show the importance of these materials for public education. Projects with the aim of improving, expanding or perfecting these materials have achieved significant results in their validations.